Development and Validation of Digital-Based Preliminary Reading Media Instruments - Kasmawati, Kasmawati; Zibar, Chairan; Sisi, La; Juwariyah, Arna; Sasmin, Sasmin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to develop digital-based learning media instruments for first graders on beginner reading materials. This method of research used research and development that uses the ASSURE model. The instrument used questionnaire and validation sheet. Data analysis techniques are performed by calculating the value of the validity test results. The results showed that; 1) A digital-based learning media in the form of audio-visual has been developed using the kinemaster application for beginning reading material for grade I elementary schools which uses 3 stages of the model, namely: Analyze Learning; State Standards and Objectives; Select Strategic Technology, Media and Materials; 2) The results of the validity test on digital-based beginning reading learning media products that have been developed, as a whole are assessed by the material validator and media design. The results of the score by material experts are 89% in the "Very Valid" category, for media design experts it is obtained with 94% in the "Very Valid" category. Thus, it can be concluded that digital-based early reading learning media in Indonesian lessons for grade I elementary schools is very valid to be used as one of the media in Indonesian subjects.